ASSESSMENT OF THE METAL ARTIFACT REDUCTION TOOL FOR THE DETECTION OF ROOT ISTHMUS IN MANDIBULAR INTRARADICULAR POSTS IN CONE-BEAM MOLARS WITH COMPUTED TOMOGRAPHIC SCANS - Oliveira, Manuela Lima Barros de; Junqueira, Rafael Binato; Kamburoğlu, Kıvanç; Eratam, Nejlan; Çakmak, Esra Ece; Sönmez, Gül; Küçük, Özlem; Verner, Francielle Silvestre (Revista de Ciência, Tecnologia e Sociedade, 2025)
The objective of the present study was to evaluate the performance of the metal artifact reduction (MAR) algorithms tool in different fields of view (FOV) of Cone Beam Computed Tomography (CBCT) for the detection of root isthmus in mandibular molars with intraradicular posts. Twenty-eight mandibular human molars were submitted to micro-computed tomography (micro-CT) exam and the data set for isthmus detection and establishment of the reference standard. The teeth were prepared for endodontic treatment and later divided into three groups: Gutta-percha Group: teeth treated endodontically, without intraradicular post (n = 10); Metal pin group: teeth treated endodontically and with prefabricated metal post (n = 9); Fiberglass post group: teeth treated endodontically and with fiberglass post (n = 9). The acquisition of CBCT images was performed by varying the size of the FOV (10 x 5.5 and 5 x 5.5 cm) and the use of the MAR tool (disabled, low, normal and high). The CBCT exams were evaluated by three specialists in Dental Radiology, who identified the presence or absence of the root isthmus in the cervical, middle and apical root thirds of the mesial root of the mandibular molars, according to a 5-point scale. When considered to be present, the isthmus was classified as complete or incomplete. To check the intra- and inter-rater agreement, the weighted Kappa test was used. To check the association between the root third and the type of isthmus, the chi-square test was used. To compare the different acquisition protocols with the reference standard it was used the McNemar test. ROC curves were constructed to obtain the values of accuracy, sensitivity and specificity. The comparison of values between the tested protocols in groups with and without post was performed using two-way ANOVA, with Tukey’s post hoc test (P <0.05). The intra- and inter-examiner agreement varied from moderate to substantial. The chi-square test showed an association between the root third and the type of isthmus (p <0.05). The frequency of correct diagnosis for assessing the root isthmus compared to the gold standard varied complementarily in all groups, regardless of the selected image acquisition protocol (P <0.05). In the gutta-percha group, there was no difference in the values of accuracy, sensitivity and specificity between the protocols tested. In the groups of metal and fiberglass posts, the accuracy values were higher with the “disabled” and “low” modes of the MAR tool, regardless of the size of the selected FOV. This was also observed for the sensitivity values in the metal post group (P <0.05). It was concluded that the size of the FOV did not affect the performance of the MAR tool and all protocols differed to the gold standard. However, the use of the MAR tool in normal and high modes produced worse results and, therefore, should be contraindicated for conditions similar to the present study.